Homeopathy and acupuncture teaching at Faculdade de Medicina da Universidade de São Paulo: the undergraduates’ attitudes - Teixeira, Marcus Zulian (2005)
CONTEXT AND OBJECTIVE: Homeopathy and acupuncture, although recognized as medical specializations in Brazil, are not taught in most medical schools. The objective was to evaluate undergraduate attitudes towards them following their inclusion as optional disciplines at Faculdade de Medicina da Universidade de São Paulo (FMUSP) in 2002. DESIGN AND SETTING: Questionnaire, at FMUSP. METHODS: 484 students answered a self-adminis- tered questionnaire on these therapies, regarding their interest in learning, the teaching methods, their knowledge/experience (or that of someone close to them) and how it was acquired, the main indicators and general effectiveness of these therapies, and the possibilities for offering and integrating them within public healthcare units. RESULTS: Over 85% of the students considered that homeopathy and acupuncture should be included in curricula, as options (72%) or com- pulsorily (19%); 56% showed great interest in learning about them. Although 76% had little or no knowledge, 67% believed that these therapies had some effectiveness, and that chronic diseases (37%) or even chronic and acute diseases (29%) would be the main indicators for their use. Around 35% were receptive towards offering public primary care using both therapies, while 34% thought these treatments should also be available in hospitals and 60% believed they could be integrated with conventional medical practices. CONCLUSION: The medical students were interested in learning the principles of homeopathy and acupuncture, were able to observe and report on the effectiveness of these treatments and defended the use of these medical specializations within public healthcare.